Aplicación de las metodologías de observación directa e indirecta en el monitoreo del Zorro Andino (lycalopex culpaeus reissii), para determinar su presencia en el nororiente y suroriente de la parroquia Aláquez - Quintana Carua, Kevin Dario (2023)
In Ecuador, the Andean fox is in a highly vulnerable state, due to high-risk factors, such as: the deforestation, population pressure, agricultural frontier extension, and indiscriminate hunting. All these components constitute the ecosystems reduction, several species displacement from their natural habitat, causing a decrease in the individual’s typical percentage each place. Through the current research, it is intended to determine the Andean wolf presence, (Lycalopex culpaeus reissii), in the moorlands from Alaquez parish (northeast and southeast), applying the method (transects, prismatics use) and indirect (signs registration: Canine’s excreta, footprints, photo cheating, surveys and technical sheets). The same ones, what are located at points within the map with respect to the studied area. With this method, it was got several location exact coordinates from presence of the Andean wolf, thus, determining areas, temperatures, climates and vegetation. Within these activities, it is analyzed the presence from Andean wolf (Lycalopex culpaeus reissii) by anthropic activities as are the agricultural and livestock frontier constant growth. Further, to the various factor’s existence, such as climate change, which the areas their habitat are not defined and this causes the species to have to adapt to various climates, being the case from Andean wolf (Lycalopex culpaeus reissii). Through the made studies, they are confirmed the presence from Andean fox in the Alaquez moorlands (northwest and southwest), starting at 3700 m.s.n.m. In the morning hours. In the study area, there is verified a feral dog’s incidence, which compete for food sources for wildlife, causing the Lycalopex culpaeus reissii displacement to other areas decreasing its population.